Millennials and Generation Z: a generational cohort analysis of Indian consumers. Issue 7 (4th February 2021) - Thangavel, Packiaraj; Pathak, Pramod; Chandra, Bibhas
Abstract : Purpose: Young consumers are recognized as an important and lucrative segment for the businesses across the globe. While initial steps have been taken to understand them, majority of the existing works consider both Millennials and Generation Z as a single and homogeneous market segment. The purpose of this study is to explore the consumer decision-making styles which are prevalent among Indian Millennials and Generation Z e-shoppers, and how significantly they differ from one another on each of those decision-making attributes. Design/methodology/approach: This exploratory study used the generational cohort theory (GCT) as a framework. The psychographic statements (Questionnaire items) employed were adopted from several past researches on store orientation and catalog orientation, and they were rephrased to suit to the context of Indian online shopping. The principal components factor analysis with promax rotation has been used to unearth the underlying decision-styles among 503 survey participants. Subsequently, the ANOVA model was run to examine the mean differences between the cohorts. Findings: The factor analysis has revealed that frugality (Price), convenience (Home) and social desirableness are the most dominant shopping orientations (decision-styles) that prevail among Indian (Millennials and Generation Z) online shoppers though in varying degrees. The probing of ANOVA results suggested that, though both the cohorts favor e-shopping, Generation Z are more enthusiastic about online shopping than their Millennial counterparts do. Practical implications: Though Generation Z and Millennials share few characteristics between them, they exhibit different consumer behaviors. Marketers need to customize their value offerings and marketing communications that resonate well with each generational cohort. Originality/value: Almost all the existing research works that have been conducted so far on generational cohorts are from Western and European countries and one could confidently say that those findings cannot be applied for the developing nations such as India which is a complex and diverse country in terms of its language, custom, religion and practices with troublesome pasts. Moreover, this is the first empirical work to be conducted to unearth the generational differences that exist between Generation Z and Millennials to the best of authors' knowledge.